Development of an Educational Website as an Interactive Learning Platform to Improve Students' Environmental - Surya Dharma; St Aisyah Humaerah; Asrul Muarif; Nursyamsi Nursyamsi (Universitas Negeri Semarang, 2026)
This research is motivated by the problem of low environmental literacy among students, and the general lack of interactive environmental literacy teaching materials in school resources. Therefore, research was conducted with the aim of developing an educational website as an interactive learning platform to improve students' environmental literacy, making it valid, practical, and effective. This research applies the research and development method by adapting the ADDIE model. The subjects of this study are students from public high schools in Gowa Regency and Makassar City, and cluster random sampling technique is used. The data collection techniques used include documentation as a literature review, expert validation sheets, tests, teacher response questionnaires, and student response questionnaires. The data analysis techniques used include Aiken's V validity analysis, descriptive statistics, and paired sample t-tests. The results of research and development yielded an educational website with the domain www.literacyenvironmentalclass.com that is valid, effective, and very practical to be applied as an interactive learning platform in improving students' environmental literacy. The implications of this study show that there has been success in developing an educational website that can encourage improvements in the quality of technology-based learning in schools, particularly in improving students' environmental literacy.